Analisis Kebjakan Deviden dan Kemampulabaan terhadap Nilai Perusahaan Studi Kasus PT. Tambang Bukit Asam Tbk dan PT. Timah Tbk - Achmad, Noor; Joyonegoro, Adi (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2010)
Companyâs purpose is to make stockholders be prosperous by creation of stock value. The creation of stocks price can be done by dividend policy and profitability. Dividend policy is finance decision by considering whether dividend payment can improve stockholderâs prosperity and considering profitability as the ability level of the company to make profit. The goal of this research is to find out the correlation of dividend policy to company value, to find out the correlation of profitability to company value, and to find out the correlation of dividend policy and profitability simultaneously to company value. Analysis method and measurement of correlation and influence between variables in this research utilize correlation coefficient, determinant coefficient, and regression coefficient. The result of this research show that (a) dividend policy and proxy dividend per share has significant correlation and influence to company value and proxy stock market value at PT Timah Tbk by significant level 0,0151. But at PT Tambang Bukit Asam Tbk., there is no significant correlation and influence by significance level 0.4448, because of external factor, that is worst economy condition. (b) Profitability and proxy earning per share has significant correlation and influence to company value and proxy stock market value at PT Timah TBC by significance level 0,0158. But there is no significant correlation and influence at PT Tambang Bukit Asam Tbk by significance level 0.4805, because of external factor such as worse economy condition. (c) dividend policy and proxy dividend per share plus profitability and proxy earning per share simultaneously have correlation and influence to company value and proxy stock market value at PT Timah TBC by significance level 0, 0635, but there is no significant correlation and influence at PT Tambang Bukit Asam Tbk by significance level 0, 1341, because of external factor such as worse economy condition. Keyword : dividend policy, profitability and company value